2022
DOI: 10.1002/mp.15934
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based virtual noncalcium imaging in multiple myeloma using dual‐energy CT

Abstract: Background: Dual-energy CT with virtual noncalcium (VNCa) images allows the evaluation of focal intramedullary bone marrow involvement in patients with multiple myeloma. However, current commercial VNCa techniques suffer from excessive image noise and artifacts due to material decomposition used in synthesizing VNCa images. Objectives: In this work, we aim to improve VNCa image quality for the assessment of focal multiple myeloma, using an Artificial intelligence based Generalizable Algorithm for mulTi-Energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…In terms of image reconstruction, some studies have found that low-kiloelectron volt VMI reconstruction via deep learning can improve image quality in the evaluation of hypoenhanced hepatic metastasis and other liver diseases ( 35 - 37 ). Furthermore, deep learning can automatically segment brain tumors and surrounding healthy tissues to assist in the diagnosis of multiple myeloma ( 38 , 39 ). It can even predict head and neck lymph node metastasis of papillary thyroid carcinoma on DECT images ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of image reconstruction, some studies have found that low-kiloelectron volt VMI reconstruction via deep learning can improve image quality in the evaluation of hypoenhanced hepatic metastasis and other liver diseases ( 35 - 37 ). Furthermore, deep learning can automatically segment brain tumors and surrounding healthy tissues to assist in the diagnosis of multiple myeloma ( 38 , 39 ). It can even predict head and neck lymph node metastasis of papillary thyroid carcinoma on DECT images ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several deep learning architectures, previously designed to solve other image processing tasks, have been deployed for image-based decomposition. Most works are based on a supervised learning approach where a dataset of manually segmented basis material images are available: fully convolutional network [127], U-Net [128]- [133], Butterfly-Net [134], visual geometry group [132], [135], Incept-net [136], [137], generative adversarial network (GAN) [138], Dense-net [139]. These contributions differ on the type of architecture adopted and the complexity of the network which is measured by the number of trainable parameters.…”
Section: A Image-based Materials Decompositionmentioning
confidence: 99%
“…They also differ in which inputs are used by the network, e.g., reconstructed multichannel CT images µ [133] or pre-decomposed CT images [131]. The network output is generally the decomposed CT images x m but it may also be other images, e.g., the elemental composition [132], quantities used for radiotherapy planning such as the image of the electron density [140] or the virtual non-calcium image [137].…”
Section: A Image-based Materials Decompositionmentioning
confidence: 99%
“…In terms of LDWBCT for the diagnosis of MM, artificial intelligence is being developed to generate tools that automatically perform segmentation and bone subtraction both in monoenergetic CT and DECT to recognize focal lesions, allowing for the quicker interpretation of results and increasing diagnostic accuracy [ 21 , 100 , 101 , 102 ], as well as creating convolutional neural networks that allow for a straight estimation of the distribution of materials, avoiding the need to perform the conventional material decomposition [ 103 ]. The development of algorithms to minimize noise and artifacts in VNCa images has yielded promising first results [ 104 ], and deep learning for photon-counting detector images has shown a greater performance in highlighting focal lesions [ 99 ].…”
Section: Future Directionsmentioning
confidence: 99%

Imaging of Multiple Myeloma: Present and Future

Rodríguez-Laval,
Lumbreras-Fernández,
Aguado-Bueno
et al. 2024
JCM